2022
DOI: 10.3389/fendo.2022.1069559
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID lockdown on glycaemic control in paediatric patients with type 1 diabetes: A systematic review and meta-analysis of 22 observational studies

Abstract: IntroductionThe COVID lockdown has posted a great challenge to paediatric patients with type 1 diabetes (T1D) and their caregivers on the disease management. This systematic review and meta-analysis sought to compare the glycaemic control among paediatric patients with T1D (aged under 18 years) pre- during, and post-lockdown period.Methods and materialsWe did a systematic search of three databases (PubMed, Embase, and the WHO COVID‐19 Global literature) for the literature published between 1 Jan 2019 to 10 Sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Studies conducted in China in 2022 and Taiwan in 2021 found no significant difference in HbA1c results between the pandemic and pre-pandemic periods. 33 , 34 Remarkably, a study conducted in Spain in 2021 instead reported improved glycaemic control during the pandemic, and this was supported by two systematic reviews and meta-analyses performed in the United Kingdom and Germany in 2021. 35 , 36 , 37 In contrast to the findings of these studies, we found a significant increase in the average HbA1c result during the pandemic of 2.2 mmol/mol (0.2%) overall and in nine of the districts, indicating poorer glycaemic control during the pandemic where decreased numbers of HbA1c tests were being conducted.…”
Section: Discussionmentioning
confidence: 93%
“…Studies conducted in China in 2022 and Taiwan in 2021 found no significant difference in HbA1c results between the pandemic and pre-pandemic periods. 33 , 34 Remarkably, a study conducted in Spain in 2021 instead reported improved glycaemic control during the pandemic, and this was supported by two systematic reviews and meta-analyses performed in the United Kingdom and Germany in 2021. 35 , 36 , 37 In contrast to the findings of these studies, we found a significant increase in the average HbA1c result during the pandemic of 2.2 mmol/mol (0.2%) overall and in nine of the districts, indicating poorer glycaemic control during the pandemic where decreased numbers of HbA1c tests were being conducted.…”
Section: Discussionmentioning
confidence: 93%
“…Many studies (involving 1498 children/adolescents) reported improved glycaemic control (including increased time-in-range, and reduced time-above-range, time-below-range and coefficient-of-variation in blood glucose levels, and lower HbA1C) during lockdown, compared with pre-pandemic values ( Table 1 ). It is believed that extra vigilance and increased compliance with medication during the pandemic could have accounted for improved glycaemic control [17] , [38*] , [40] , [48] . However, four other studies involving 465 children/adolescents with type 1 diabetes reported worsened glycaemic control during the pandemic [15] , [33] , [34] , [43] ( Table 1 ).…”
Section: Condition Specific Findings and Discussionmentioning
confidence: 99%
“…The recent meta-analysis by Han et al [ 55 ], which collected data of 2106 pediatric patients including the afore-mentioned studies, confirmed that, as a whole and compared with the pre-lockdown period, glucose had significantly decreased both during and after lockdown. Furthermore, the improvement was also found for many metrics, i.e.…”
Section: Metabolic Controlmentioning
confidence: 90%